Neonatal Spontaneous Bilateral Posterior Fossa Chronic Subdural Hematoma and Obstructive Hydrocephalus with a Successful Outcome: A Case Report - Bergene E; Tira AE; Hussen E; Smith CJ; Fetle YT (International Medical Case Reports Journal, 2023)
Eyerusalem Bergene,1 Abdi Ermolo Tira,2 Endris Hussen,1 Caitlyn J Smith,3 Yonas T Fetle4 1Department of Neurosurgery, St. Paul’s Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Neurosurgery, St. Peter’s Comprehensive Specialized Hospital, Addis Ababa, Ethiopia; 3Department of Neurosurgery, University of Missouri School of Medicine, Columbia, MO, USA; 4Department of Neurosurgery, Addis Ababa University College of Health Science, Addis Ababa, EthiopiaCorrespondence: Eyerusalem Bergene, Email monorovia@gmail.comBackground: Chronic supratentorial subdural hematoma is uncommon in neonates but accounts for most neurosurgical procedures in neonatal age. However, its occurrence in the posterior fossa is extremely rare. It can be caused by instrumental delivery, coagulation abnormality, hypoxic insult, and various structural abnormalities. Furthermore, spontaneous onset has been reported only in a few case reports.Case Presentation: A twenty-nine-day-old male neonate presented with failure to suck for three days duration associated with vomiting. Imaging showed bilateral posterior fossa chronic subdural hematoma and obstructive hydrocephalus. Bilateral burrhole craniostomy and hematoma evacuation was done which resulted in an excellent outcome.Conclusion: Posterior fossa chronic subdural hematoma is extremely rare in the neonatal period. It can be caused by various possible etiologic agents; however, rarely it can occur spontaneously. Management with suboccipital burrhole craniostomy and hematoma evacuation can result in a good outcome. Intraoperative monitoring and management with an experienced anesthesiology team are indispensable for a good outcome.Study Setting: Pediatrics neurosurgery ward, St Peter’s Comprehensive Specialized Hospital, Addis Ababa, Ethiopia.Keywords: posterior fossa, chronic, subdural hematoma, neonate